Evaluation of the Effectiveness of Hybrid Learning Based on Linear Algebraic Hybrid Model in the Online-Offline Lecture System in the Digital Era - Andre Meyro Ritonga; Nicholas Sulistio; Guruh Pandhu Anggriawan; Mohamad Yusuf (Journal Collabits, 2025)
Optimal class division is a crucial aspect of academic planning to ensure the effectiveness of the learning process. The main challenges in class division lie in the limited capacity of space, balanced distribution of students, and the fulfillment of varied academic needs. This study proposes a Linear Programming-based approach to optimize class division by considering various constraints, such as the maximum capacity of the room, the number of students, and the distribution of subjects according to curriculum needs. The developed applications are designed to produce optimal solutions that minimize student distribution gaps and ensure efficient classroom utilization. A case study is applied to an educational institution to evaluate the performance of the application in real situations. The results of the experiment show that this approach is able to improve the efficiency of classroom allocation, reduce imbalances in the distribution of students, and optimize the use of educational facilities. Thus, this research contributes to more effective and data-based academic management in decision-making related to class division.